The question is given below as
![x^2+3x-18=0](https://img.qammunity.org/2023/formulas/mathematics/college/w6r70yzq6xvz8zp5cgnbpfc5ie294vcyer.png)
Step 1:We will look for two factors we will multiply together to get -18 and the same two factors that will add up together to +3
![\begin{gathered} The\text{ factors of 18 are} \\ 1,-1,2,-2,3,-3,6,-6,-9,9,18,-18 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8k982owwa2cgr66qaa4yngw97sqqtlyf50.png)
Since -18 is a negative value
Then, the two factors must have different signs because of the sign pattern below
![\begin{gathered} -*-=+ \\ +*-=- \\ +*+=+ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4fdnfd0b57pzew9mr8j1f6a2idh37xndwd.png)
The two factors are
![\begin{gathered} +6,-3 \\ +6*-3=-18 \\ +6-3=+3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zt3yv8rtdr4odaw7k9jdrznicgxeraiufc.png)
Step 2: Substitute the factors in the equation below
![\begin{gathered} x^2+3x-18=0 \\ x^2+6x-3x-18=0 \\ x(x+6)-3(x+6)=0 \\ (x-3)(x+6)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xydrvoh3g44gs1mhfw7atgecb9xg1qgbxm.png)
Step 3: Equate both factors to zero
![\begin{gathered} (x-3)=0,(x+6)=0 \\ x=0+3,x=0-6 \\ x=3,x=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5solpxygjinwz46m9094foo9cod2csmzpo.png)
Hence,
The final answer are x =3 and x = -6